Introduction of Luminol-dependent Chemiluminescence as a Method to Study Silica Inflammation in the Tissue and Phagocytic Cells of Rat Lung - J. M. Antonini; K. Van Dyke; Z. Ye; M. DiMatteo; M. J. Reasor (The National Institute for Occupational Safety and Health (NIOSH), 1995)
"The inhalation of silica has been shown to produce a dramatic inflammatory and toxic response within the lungs of humans and laboratory animals. A variety of cellular and biochemical parameters are used to assess the silica-induced lung injury. The purpose of this paper is to introduce the use of luminok:Jependent chemiluminescence as a new method to study inflammation in both phagocytic cells and lung tissue recovered from silicaexposed animals. Chemiluminescence, or the emission of light, accompanies the release of reactive forms of oxygen when phagocytic cells are challenged. In this study, male Fischer 344 rats were intratracheally instilled with either silica (10 mg/100 g bw) or saline vehicle. One day after the instillations. a marked increase in the chemiluminescence was observed in the lung tissue and bronchoalveolar lavage cells recovered from the silica- treated animals when compared with the saline controls. The light reaction was markedly decreased by either superoxide dismutase or N-nitro-Larginine methyl ester hydrochloride. Superoxide dismutase is involved in the enzymatic breakdown of superoxide anion. while N-nitro-L-arginine methyl ester hydrocholoride, a nitric oxide synthase inhibitor, prevents the formation of nitric oxide. When superoxide anion and nitric oxide react. they form the highly oxidizing substance peroxynitrite. This study then implicates peroxynitrite as an agent that may be responsible for some of the oxidant lung injury that is associated with silica exposure. The use of luminol-dependent chemiluminescence may prove valuable as a method to measure the earliest events in the inflammatory process. and may be an adjunct in studying the mechanisms that produce inflammation. - Environ Health Perspect 102(Suppl 10):37-42 (1994) IntroductionResearch on inflammation has not produced a method that links the initial events of the process to the controlling events. Rather, a variety of parameters are measured that are the result of and not the basis of the inflammatory reaction. Parameters such as tissue weight, edema, blood flow, enzyme and protein release, or production of metabolites (prostaglandins, leukotrienes) have been used extensively. A method is needed that could be applied to cells of a particular type, groups of cells of different types, and even tissue, in an attempt to study the kinetics of the inflammation as well as being sensitive enough to monitor the early events of the process . Since inflammation is so complicated, the relationship between the control of the initial events and the oxidation process has never been explained nor studied in any derail."